[Rezension von: Hasel, Frank, 1962-, Biblical Hermeneutics : An Adventist Approach] - Lukić, Marko (Spes christiana, 2021)
This book was born as an answer to an issue raised from the floor at the 2015 General Conference (GC) Session in San Antonio, Texas (pp. 2‒4). The discussion of women’s ordination led to the observation that Seventh-day Adventists are drawing different conclusions from the same Scriptures. In attempts to explain this reality, it was proposed that there coexist two different hermeneutics within the world church and that it would be necessary to address this confusion. Therefore, as the answer to the request, the Biblical Research Institute has produced this book. The proclaimed goal of this work is to present an approved Adventist hermeneutic that could be accepted by the global church.